Delivering the digital restaurant the path to digital maturity - Sandland, Meredith
"The duo that explained the digital revolution in restaurants now brings your restaurant a how-to guide. The digital restaurant revolution is well underway. Restaurants that survived the pandemic now have the opportunity to step back and consider how to best serve digital demand.